Molecular analysis of aggressive renal cell carcinoma with unclassified histology reveals distinct subsets - Ying-Bei Chen (Nature Portfolio, 2016)
A subset of renal cell carcinomas have uncertain histology and are aggressive in nature. Here, the authors examine this group of unclassified renal cancers using genomics techniques and identify further subclasses of the tumours that have differing prognoses.